The problem of self-realization of a teacher’s personality in professional activity - Tursynbet, G.T.; Kipshakov, S.A.; Danek, J. (Buketov University, 2024)
The relevance of the article is generated by the fact that the structure of the newest domestic education system is continuously being reformed and improved. This is intertwined with many innovative and globalizing processes in our society. This means quite rapid and serious transformations in this field of activity at the level of serious transformations in terms of approach to professional activity, its implementation and its specific and probable prospects in it. That is, we are talking about the concept of self-realization of a teacher of educational activity. Therefore, the study and resolution of this problem is very relevant for the current pedagogical psychology. The purpose of this article is a theoretical understanding of the main scientific content of the definition of “self-realization” and “self-realization of the teacher's personality”, the solution of which will be carried out through the following tasks: scientific and theoretical analysis of the concepts “self-realization” and “self-realization of the teacher's personality” taking into account a variety of theoretical approaches in pedagogy and psychology, substantiation of the features of self-realization of a teacher's personality in professional activity, practical verification of the level of self-realization of teachers based on methodical approaches. The article clarifies the scientific content of the definition of “self-realization”, the content of such definitions as “professional activity”, “professional and pedagogical activity”, “self-development”.
Кәсіби іс-әрекетте педагог тұлғасының өзін-өзі жетілдіру мәселесі
Проблема самореализации личности педагога в профессиональной деятельности
Keywords: self-realization of personality; professional activity; self-development; professional pedagogical activity; self-study; self-realization; self-understanding; autosympathy